Integrated nutrient management of mustard greens (Brassica juncea), variety Pusa Sag-1 under terai region of West Bengal - RAHIM, ABDUR; JANA, J C (The Indian Journal of Agricultural Sciences, 2026)
A field experiment was carried out during the rabi seasons of 2022–23 and 2023–24 to evaluate the integrated effects of organic amendments and microbial inoculants combined with reduced inorganic fertiliser rates such as 75% and 50% recommended dose of fertilisers (RDF) on the agronomic performance of mustard greens (Brassica juncea L.), including vegetative growth, fresh yield and biochemical quality parameters. The study was conducted using a randomised complete block design comprising 16 treatment combinations with three replications, employing the Pusa Sag-1 cultivar. Results revealed that the application of 75% RDF + 4 t VC/ha + 5 kg Azotobacter/ha + 5 kg PSB/ha (T9) recorded significantly maximum plant height (49.96 cm), leaf length (44.39 cm), leaf width (14.06 cm), number of leaves/plant (10.77), leaf yield/plant (128.36 g), dry weight of leaves/plant (13.88 g), green yield (29.92 t/ha). This treatment also showed superior quality parameters/100 g fresh weight, including ascorbic acid (30.53 mg), total chlorophyll (60.34 mg) and β-carotene (2524.45 µg) of mustard greens. Additionally, this treatment enhanced available soil nutrients including nitrogen (195.26 kg/ha), phosphorus (26.61 kg/ha) and potassium (101.22 kg/ha), while achieving the most favorable benefit-cost ratio of 3.48:1. Integrated application of chemical fertilisers with vermicompost and biofertilisers significantly improved mustard green’s yield attributes, quality parameters and soil fertility status, facilitating sustainable intensification of production.